(untitled) (Journal of Hama University, 2024)
The research aimed to determine the role of the five major factors of the leader’s personality (emotional balance, extraversion, acceptance, Openness to experience and expertise, vigilance of conscience) in crisis management in the administrative development directorates. The researcher adopted the descriptive analytical approach, Where the statistical analysis program 25 Spss was used to analyze the data collected using the questionnaire method, while the research sample was (74) individuals, The most important findings of the study are the existence of a positive role for the personal characteristics of the leader in crisis management in the administrative development directorates, Based on the previous results, the researcher recommended the need to pay attention to the inclusion of behavioral sciences and crisis sociology in the curricula of various university majors, and taking into account specific criteria when selecting qualified individuals to fill leadership positions, as they will have a pivotal role in making crisis management decisions quickly and more decisively.